The Implementation of Web-GIS in Developing Tourism Object in Langkat Regency with Location Based Service Method - Surya Hendra Putra; Evan Afri (IJISTECH (International Journal of Information System and Technology), 2020)
This research aims to help out the Culture and Tourism Office of Langkat Regency in presenting Langkat Regency tourism objects widely across the globe through the web. Therefore, it can be trusted to be able to increase the number of both domestic and foreign tourists to visit Langkat Regency. This research shows a digital map on the web using the Google Maps API. With the belief that with there is an app that can clearly and completely displaying the name, photo, description and location of tourist objects which are taken from the database contained in the Google DBMS, it can increase the prospect of the number of tourists coming to Langkat Regency. Given that Langkat Regency has excellent tourism potential. One of them is the Bukit Lawang area which has captivity for orangutans, then which are endangered and endangered by elephant captivity. With web-GIS using the Location-Based Service (LBS) method by utilizing Google Maps API technology and the CodeIgniter Framework. With LBS, the coordinates of tourist locations in the form of latitude and longitude derived from the Google Maps application can be easily entered in the webGIS code structure.